2003
DOI: 10.1081/ese-120022873
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Evaluation of Select Nitrate Removal Technologies

Abstract: Due to the extensive application of artificial nitrogen-based fertilizers and animal manure on land, many water agencies face problems of increasing concentrations of nitrate in groundwater. The contamination of groundwater by nitrate may pose a significant public health problem. The threat of methemoglobinemia is well documented and reflected in the US drinking water standard of 10 mg/L as nitrate-nitrogen. Approximately 45% of Saskatchewan's population use groundwater for drinking purposes, out of which, app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…A wide variety of treatment options for nutrient runoff have been developed. These include riparian buffer zones, biofilters, denitrification walls and constructed wetlands (Bezbaruah and Zhang, 2003;Darbi et al, 2003;Jaynes et al, 2008;Kelly et al, 2007;Lin et al, 2007;Su and Puls, 2007;Vymazal, 2007;Yamada et al, 2007). Although each of these systems has been shown to reduce the NO 3 -N concentration in groundwater, there is no single ideal system appropriate for use under all circumstances.…”
Section: Fig 4 Reactive (Ortho) Phosphate In Rvfb Effluentmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of treatment options for nutrient runoff have been developed. These include riparian buffer zones, biofilters, denitrification walls and constructed wetlands (Bezbaruah and Zhang, 2003;Darbi et al, 2003;Jaynes et al, 2008;Kelly et al, 2007;Lin et al, 2007;Su and Puls, 2007;Vymazal, 2007;Yamada et al, 2007). Although each of these systems has been shown to reduce the NO 3 -N concentration in groundwater, there is no single ideal system appropriate for use under all circumstances.…”
Section: Fig 4 Reactive (Ortho) Phosphate In Rvfb Effluentmentioning
confidence: 99%
“…Therefore, the efficiency of surface systems for treatment may be reduced because substantial amounts of contaminated water may bypass the active treatment zone. To address this limitation, subsurface systems such as in-situ bioreactors, permeable reactive barriers, biofilters, and subsurface flow constructed wetlands have been investigated (Bezbaruh and Zhang, 2003;Darbi et al, 2003;Greenan et al, 2006;Robertson et al, 2007;Schipper and Vojvodic-Vakovic, 2000;Schipper and Vojvodic-Vakovic, 2001;Schipper et al, 2004;Su and Puls, 2007;van Driel et al, 2006). These subsurface systems generally depend on microbial denitrification to mineralize and remove nitrate.…”
Section: )mentioning
confidence: 99%
“…• In "Pilot-Scale Evaluation of Select Nitrate Removal Technologi,es" (Darbi et al 2003), a field study demonstrated that approximately 65 mg-NIL nitrate could be treated to an average concentration of 6.1 mg-NIL. The IX system used a strong-base anion-exchange Electrodialysis has been demonstrated to be capable of removing nitrate from groundwater ("Pollution of Nitrate in Moroccan Ground Water: Removal by Electrodialysis" [Elmidaoui et al 2001]; "Experience with Full-Scale Electrodialysis for Nitrate and Hardness Removal" [Hell et al 1998]; "Removal of Nitrate by Electrodialysis" [Indusekhar et al 2001 Reverse osmosis is often referred to as a common technology for the treatment of nitrate using pump-and-treat, although the published number of articles are limited.…”
Section: Physical/chemical Treatmentmentioning
confidence: 99%
“…The IX system used a strong-base anion-exchange Electrodialysis has been demonstrated to be capable of removing nitrate from groundwater ("Pollution of Nitrate in Moroccan Ground Water: Removal by Electrodialysis" [Elmidaoui et al 2001]; "Experience with Full-Scale Electrodialysis for Nitrate and Hardness Removal" [Hell et al 1998]; "Removal of Nitrate by Electrodialysis" [Indusekhar et al 2001 Reverse osmosis is often referred to as a common technology for the treatment of nitrate using pump-and-treat, although the published number of articles are limited. Published literature includes demonstrations of field studies that showed treatment of 65 mg··NIL nitrate to an average concentration of7.7 mg-NIL (Darbi et al 2003), treatment of 42..5 mg/L of nitrate to 0.9 mg/L ("Nitrate Removal with Reverse Osmosis in a Rural Area in South Africa" [Schoeman and Steyn 2003]), and treatment to achieve 75% to 95% nitrate removal in reverse osmosis plants with 76 and 100 mg/L nitrate ("Use of Reverse Osmosis for Removal of Nitrate in Drinking Water" [Bilidt 1985]). …”
Section: Physical/chemical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation